Evaluation of the Activities of Commonly Dispensed Antibiotics at Bayero University Kano Health Care Services Unit (Sahel Journal of Life Sciences FUDMA, 2024)
There is a growing concern about the effectiveness of antimicrobials in developing countries. Multifaceted factors contribute to the escalation of antibiotic resistance. The counterfeiting of antibiotic drugs is one facet of this. Antibiotics are the most counterfeited medicines worldwide. However, the WHO Committee for the review of Medicines accentuates surveillance checks even after the marketing of drugs or at the dispensing point. This study evaluated the activities of commonly dispensed antibiotics at Bayero University Kano health care service pharmacy unit. Fourteen brands of different antibiotics with the active ingredients amoxicillin, azithromycin, cefixime, ceftriaxone, ofloxacin, ciprofloxacin, and doxycycline were used. The antibiotic susceptibility testing was carried out using the Kirby Bauer disc diffusion method on clinical isolates of Escherichia coli, Staphylococcus aureus and Klebsiella pneumoniae. Typed strains of E. coli (ATCC 25923) and S. aureus (ATCC 25922) were also tested. Ciprofloxacin and ofloxacin-containing formulations had efficacy against all the clinical isolates and typed organisms. All organisms except K. pneumoniae were sensitive to azithromycin. Ceftriaxone was active only against E. coli (both clinical isolate and typed organism). About 71% of the antibiotics tested were not sensitive to the tested organisms.Â  The inactivity observed may be due to the counterfeit or substandard nature of the antibiotics, ineffective storage, or the development of resistance. This necessitates more research to determine the extent of the problem and its causes at a large scale.